2011
DOI: 10.1007/s00210-011-0637-7
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibition suppresses the development of lung fibrosis in the bleomycin model

Abstract: The extracellular signal-regulated kinase (ERK) cascade has long been known to be central to the activation of cellular processes such as proliferation, differentiation, and oncogenic transformation. The mitogen-activated protein (MAP) serine/threonine family of protein kinases, of which ERK is a member, is activated by a mechanism that includes protein kinase cascades. Mitogen-activated protein kinases (MAPKs) are well-conserved enzymes connecting cell surface receptors to intracellular regulatory targets; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 46 publications
3
36
0
1
Order By: Relevance
“…Blockade of the ERK pathway by a small molecule inhibitor reduced inflammation and fibrosis in the mouse bleomycin model (47), and Yoshida and colleagues reported that, compared with control subjects, activated ERK signaling is significantly increased in lung homogenates from patients with IPF (44). It has also been reported that the methyl ester derivative of CDDO can inhibit the ERK pathway in leukemia cells (48) and that 15d-PGJ 2 can inhibit the ERK pathway in human gd T cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the ERK pathway by a small molecule inhibitor reduced inflammation and fibrosis in the mouse bleomycin model (47), and Yoshida and colleagues reported that, compared with control subjects, activated ERK signaling is significantly increased in lung homogenates from patients with IPF (44). It has also been reported that the methyl ester derivative of CDDO can inhibit the ERK pathway in leukemia cells (48) and that 15d-PGJ 2 can inhibit the ERK pathway in human gd T cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…BLM has been shown to be a stimulator of iNOS expression and NO over-production (39)(40)(41). Increased pulmonary expression of iNOS and increased NO production are observed in PF patients; however, no changes in the levels of other NOSs have been detected (22,42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that inhibition of the ERK1/2 pathway by PD98059 markedly reduced bleomycin induced lung fibrosis and TGF-β 1 induced proliferation of lung fibroblasts [Galuppo et al 2011;Jiang and Guan. 2009].…”
Section: Effect Of Cgrp On Tgf-β 1 -Induced Cell Proliferation and Exmentioning
confidence: 99%